The Role Of The National Police In Preventing And Handling The Crime Of Violent Theft (Begal) In The Jurisdiction Medan Police - Fransma Putra Laia; Janpatar Simamora; Ojak Nainggolan (UNIVERSITAS PAKUAN, 2026)
This study examines the role of the National Police in preventing and handling violent theft (begal) in the jurisdiction of the Medan Police through preventive and repressive efforts. The crime of theft with violence or often referred to as the crime of theft is a criminal act that is preceded, accompanied, or followed by violence or threats of violence against people, with the intention of preparing or facilitating theft. This crime of theft with violence has been expressly regulated in Article 365 of Law Number 1 of 1946 concerning Criminal Law Regulations which is updated by Law Number 1 of 2023 concerning the Criminal Code. This research method uses a juridical-normative approach with an empirical method. The data of this study is sourced from the results of direct interviews with law enforcement officials at the Medan Police, namely the Head of the Jatanras Unit and the Jatanras Investigator of the Medan Police which are supported by primary legal sources, secondary legal sources and tertiary legal sources as well as literature studies. Keywords: Law Enforcement, Crime, Theft, Violence, City of Medan.